ASSESSMENT OF RURAL HOUSEHOLDS FOOD INSECURITY DURING COVID-19 PANDEMIC IN SOUTH-EAST NIGERIA - EGWUE, Ogechi Lynda; AGBUGBA, Ikechi Kelechi; MUKAILA, Ridwan (International Journal of Research -GRANTHAALAYAH, 2021)
The problem of food insecurity remains a challenge in developing countries, especially in rural areas. Despite the rising level of food insecurity, COVID-19 set in and was said to pose a threat to food security globally if adequate measures are not quickly put in place. This study, therefore, described the socio-economic characteristics of the respondents; examined the extent to which the rural households are food secure or otherwise during the COVID-19 pandemic and examine the drivers of food security status among rural households in South-East Nigeria. Primary data were collected from 200 households with the use of structured questionnaires. Data were analysed using descriptive statistics, food security index and logistics regression. Results of the findings revealed that the majority of the household heads were male (92%), married (93.5%), educated (87.5%) and had an average age of 54 years. They had an average household size of 7 persons, an average farming experience of 22 years, an average monthly income of N14, 305.5 and majority (83%) do not belong to a cooperative society. Majority (69.5%) of the households were food insecure, while only (30.5%) were food secure. The food-secure households had an average household size of 5 persons, while the food insecure households had 9 persons in their households. The headcount ratio of food secure households was 0.30, while it was 0.70 for food-insecure households. This shows that at least two out of three persons were food insecure in the study area. The surplus/shortfall index indicates that the food secure households exceeded the calorie requirement by 12%, while the food insecure fell short of the recommended calorie intake by 39%. Square food insecure gap or square shortfall index which indicate the severity of food insecurity among the food insecure household was 0.0056. The average calorie available (adult equivalent per day) for food secure households was 2523.5kcal, while average calorie available (AE/day) for food-insecure households was 1389.05kcal. The identified positive drivers of food security were marital status, educational level, cooperative members and annual income of the household heads. While, age of household head, household size and COVID-19 negatively influenced food security status. The study recommends, among others, putting in place immediate policy measures to reduce the effect of COVID-19 pandemic on rural household’s food security through the provision of enough palliatives which should be monitored so that it gets to the targeted population. Effective household size management and enlightenment programs on modern family planning techniques should be encouraged in rural areas. Rural households should also be educated on the nutritional implication of the various food items such as egg, milk, soybean and fish, especially for children to increase their protein intake and boost their immune system against COVID-19.